Transcriptomic Profiles Reveal the Interactions of Cd/Zn in Dwarf Polish Wheat (Triticum polonicum L.) Roots - Wang, Yi; Wang, Xiaolu; Wang, Chao; Peng, Fan; Wang, Ruijiao; Xiao, Xue; Zeng, Jian; Kang, Houyang; Fan, Xing; Sha, Lina; Zhang, Haiqin; Zhou, Yonghong (Frontiers in Physiology, 2017)
Different intra- or interspecific wheat show different interactions of Cd/Zn. Normally, Zn has been/being widely utilized to reduce the Cd toxicity. In the present study, the DPW seedlings exhibited strong Cd tolerance. Zn and Cd mutually inhibited their uptake in the roots, showed antagonistic Cd/Zn interactions. However, Zn promoted the Cd transport from the roots to shoots, showed synergistic. In order to discover the interactive molecular responses, a transcriptome, including 123,300 unigenes, was constructed using RNA-Sequencing (RNA-Seq). Compared with CK, the expression of 1,269, 820, and 1,254 unigenes was significantly affected by Cd, Zn, and Cd+Zn, respectively. Only 381 unigenes were co-induced by these three treatments. Several metal transporters, such as cadmium-transporting ATPase and plant cadmium resistance 4, were specifically regulated by Cd+Zn. Other metal-related unigenes, such as ABC transporters, metal chelator, nicotianamine synthase (NAS), vacuolar iron transporters (VIT), metal-nicotianamine transporter YSL (YSL), and nitrate transporter (NRT), were regulated by Cd, but were not regulated by Cd+Zn. These results indicated that these transporters participated in the mutual inhibition of the Cd/Zn uptake in the roots, and also participated in the Cd transport, accumulation and detoxification. Meanwhile, some unigenes involved in other processes, such as oxidation-reduction, auxin metabolism, glutathione (GSH) metabolism nitrate transport, played different and important roles in the detoxification of these heavy metals.